# Find Three Ordered Pair Solutions 2x+3y=-4

2x+3y=-4
Solve the equation for y.
Subtract 2x from both sides of the equation.
3y=-4-2x
Divide each term by 3 and simplify.
Divide each term in 3y=-4-2x by 3.
3y3=-43+-2×3
Cancel the common factor of 3.
Cancel the common factor.
3y3=-43+-2×3
Divide y by 1.
y=-43+-2×3
y=-43+-2×3
Simplify each term.
Move the negative in front of the fraction.
y=-43+-2×3
Move the negative in front of the fraction.
y=-43-2×3
y=-43-2×3
y=-43-2×3
y=-43-2×3
Choose any value for x that is in the domain to plug into the equation.
Choose 0 to substitute in for x to find the ordered pair.
Remove parentheses.
y=-43-2(0)3
Simplify -43-2(0)3.
Simplify each term.
Cancel the common factor of 0 and 3.
Factor 3 out of 2(0).
y=-43-3(2⋅(0))3
Cancel the common factors.
Factor 3 out of 3.
y=-43-3(2⋅(0))3(1)
Cancel the common factor.
y=-43-3(2⋅(0))3⋅1
Rewrite the expression.
y=-43-2⋅(0)1
Divide 2⋅(0) by 1.
y=-43-(2⋅(0))
y=-43-(2⋅(0))
y=-43-(2⋅(0))
Multiply 2 by 0.
y=-43-0
Multiply -1 by 0.
y=-43+0
y=-43+0
y=-43
y=-43
Use the x and y values to form the ordered pair.
(0,-43)
(0,-43)
Choose 1 to substitute in for x to find the ordered pair.
Remove parentheses.
y=-43-2(1)3
Simplify -43-2(1)3.
Multiply 2 by 1.
y=-43-23
Combine the numerators over the common denominator.
y=-4-23
Subtract 2 from -4.
y=-63
Divide -6 by 3.
y=-2
y=-2
Use the x and y values to form the ordered pair.
(1,-2)
(1,-2)
Choose 2 to substitute in for x to find the ordered pair.
Remove parentheses.
y=-43-2(2)3
Simplify -43-2(2)3.
Multiply 2 by 2.
y=-43-43
Subtract 43 from -43.
y=-2(43)
Multiply -2(43).
Combine -2 and 43.
y=-2⋅43
Multiply -2 by 4.
y=-83
y=-83
Move the negative in front of the fraction.
y=-83
y=-83
Use the x and y values to form the ordered pair.
(2,-83)
(2,-83)
These are three possible solutions to the equation.
(0,-43),(1,-2),(2,-83)
Find Three Ordered Pair Solutions 2x+3y=-4